Two decimals equivalent to 8.1 are 8.100 and 8.10. Zeroes added after the decimal do not change the value. 08.1 is also equivalent to 8.1 as a zero before the decimal does not alter the value.
Explanation:Two decimals equivalent to 8.1 could be represented as 8.100 and 8.10. The reason for this is that adding zeros at the end of a decimal does not change its value. So, 8.100, 8.10, and 8.1 all represent the same decimal value.
Similarly, we can place a zero before the decimal, then 08.1 would be equivalent to 8.1. Note that the zero that comes before the decimal point does not change the actual value of the number.
Learn more about Equivalent Decimals here:https://brainly.com/question/36812284
#SPJ11
Find the slope. If you don't know the answer, don't waste my points, please.
please help asap 25 pts
[tex]4(k+5)=2(9k-4)\qquad|\text{use distributive property}\\\\(4)(k)+(4)(5)=(2)(9k)+(2)(-4)\\\\4k+20=18k-8\qquad|\text{subtract 20 from both sides}\\\\4k=18k-28\qquad|\text{subtract 18k from both sides}\\\\-14k=-28\qquad|\text{divide both sides by -14}\\\\\boxed{k=2}\to\boxed{d.}[/tex]
30 pointssssssssssssssssssssssssssssssssssssss
Answer: C
Step-by-step explanation:
"Commute" means travel so commutative property is when one of the terms or parentheses move elsewhere in the expression: 72 + (28 + 93) = (28 + 93) + 72
"Associate" is partner so associative property is when the parentheses switch partners but the order of the terms remains the same: 72 + (28 + 93) = (72 + 28) + 93
The operation between the terms is addition.
Answer:
B
Step-by-step explanation:
Hole
The question is in the attached below , thank you for helping me .
I' just going to type some of it so if there is someone in the future can find it
3. AB ~= CE
4. CE ~= AC
5. Definition of isosceles triangle
6. Transitive Property of Congruence
which of the binomials below is a factor of this expression? 121A2-64B2
A. 121A+8B
B. 11A+32B
C. 121A +32B
D. 11A+8B
Answer: 11A + 8B
Step-by-step explanation:
A triangle has side lengths of 6, 8, and 5. Is it a right, acute or obtuse triangle
Please help with geometry homework!!!!!
Answer: First option 120 sq.in
Solution:
Perimeter of the base of the prism: p=20"=20 in
Height of the prism: h=6"=6 in
Lateral area of the prism: Al=?
Al=p*h
Replacing the known values in the formula above:
Al=(20 in)*(6 in)
Al=120 sq.in
The driver of a car travels 150 miles to reach his destination. If he travels 60.0 mi/h for 100.0 miles and 55.0 mi/h for the remaining 50.0 miles, how long does it take for him to reach his destination
I think the answer is 2.7 hours
Using the formula Time = Distance ÷ Speed, we find that the driver would spend approximately 1.67 hours on the first 100 miles and 0.91 hours on the last 50 miles. Adding these two times gives a total travel time of approximately 2.58 hours.
Explanation:The first thing you need to do is calculate the time spent in each part of the trip. To calculate time, we use the formula Time = Distance ÷ Speed. For the first 100 miles at 60 mi/h, it takes: Time = 100 miles ÷ 60 mi/h = 1.67 hours. Moving on to the next 50 miles at 55 mi/h, it takes: Time = 50 miles ÷ 55 mi/h = 0.91 hours.
Adding these two times together gives us the total time for the trip: 1.67 hours + 0.91 hours = 2.58 hours. So, the driver would take approximately 2.58 hours to reach his destination if he traveled 100 miles at 60 mi/h and the remaining 50 miles at 55 mi/h.
Learn more about Speed and Time Calculations here:https://brainly.com/question/38034168
#SPJ3
Consider two functions: g(x)=x2 and the linear function f(x) with slope 1 and y-intercept of 0.
Which statements are true?
Select each correct answer.
f(−1) is equal to g(−1) .
f(1) is equal to g(1) .
f(x) is greater than g(x) on the interval (0,1) .
g(x) has a greater y-intercept than f(x) does.
ANSWER
The correct answers are option B and C
EXPLANATION
A linear function with slope [tex]m=1[/tex] and y - intercept [tex]0[/tex] has equation, [tex]f(x)=x[/tex]
Option A
[tex]f(-1)=-1[/tex]
[tex]g(-1)=(-1)^2=1[/tex]
Therefore [tex]f(-1) \ne g(-1)[/tex]
Option B
[tex]f(1)=1[/tex]
[tex]g(1)=(1)^2=1[/tex]
Therefore [tex]f(1) = g(1)[/tex]
Option C
[tex]f(0.5)=0.5[/tex]
[tex]g(0.5)=(0.5)^2=0.25[/tex]
Therefore [tex]f(x) > g(x)[/tex]
on [tex](0,1)[/tex] See graph also.
Option D
At y-intercept, [tex]x=0[/tex]
This implies that,
[tex]f(0)=0[/tex]
[tex]g(0)=(0)^2=0[/tex]
Therefore g(x) does not have a greater y-intercept.
The function f(x) with a slope of 1 and a y-intercept of 0 is compared with the quadratic function g(x)=x^2. f(1) is equal to g(1) and f(x) is greater than g(x) on the interval (0,1).
Explanation:The function g(x)=x^2 is a quadratic function, and the function f(x) with a slope of 1 and a y-intercept of 0 is a linear function. Let's evaluate the given statements:
f(-1) is equal to g(-1). To evaluate this, substitute -1 into both functions: f(-1) = -1(1) + 0 = -1, and g(-1) = (-1)^2 = 1. Since -1 is not equal to 1, this statement is false.f(1) is equal to g(1). Again, substitute 1 into both functions: f(1) = 1(1) + 0 = 1, and g(1) = 1^2 = 1. Since 1 is equal to 1, this statement is true.f(x) is greater than g(x) on the interval (0,1). To determine this, we need to compare the values of f(x) and g(x) on the interval (0,1). Evaluating both functions at x = 0.5, we get f(0.5) = 0.5(1) + 0 = 0.5 and g(0.5) = 0.5^2 = 0.25. Since 0.5 is greater than 0.25, this statement is true.g(x) has a greater y-intercept than f(x) does. The y-intercept of g(x) is 0, and the y-intercept of f(x) is also 0. Therefore, this statement is false.In summary, the true statements are: f(1) is equal to g(1), and f(x) is greater than g(x) on the interval (0,1).
Learn more about Comparing linear and quadratic functions here:https://brainly.com/question/13081013
#SPJ3
What is the explicit formula for this geometric sequence
27,9,3,1
Answer:
an=27*(1/3)^(n-1)
Step-by-step explanation:APEX
The correct option is B.
Geometric Progression,A geometric progression is a sequence in which every next term of the sequence is found out by multiplying the previous term by a fixed ratio.
Any nth term of the sequence is found out the formula,
[tex]a_n = a_1 \times r^{n-1}[/tex],
where,
[tex]a_n[/tex] is the nth term,
[tex]a_1[/tex] is the first term,
r is the fixed common ratio.
Given to us,Sequence, 27, 9, 3, 1.
the first term, [tex]a_1[/tex]= 27,
As we can see from the series 27, 9, 3, 1. the series is a geometric series,
And can be written as [tex]3^3,\ 3^2,\ 3^1\ ,3^0[/tex].
therefore, will follow the formula of a geometric series.
[tex]a_n = a_1 \times r^{n-1}[/tex],
Ratiowe know the value of r can be found out using the formula,
[tex]r = \dfrac{a_{n}}{a_{n-1}}}[/tex]
taking n =2,
[tex]r = \dfrac{a_{2}}{a_{2-1}}} = \dfrac{a_{2}}{a_{1}}}= \dfrac{9}{27} = \dfrac{1}{3}[/tex]
SubstitutingSubstituting the values in the formula of geometric progression we get,
[tex]a_n = a_1 \times r^{n-1}\\a_n = 27\times {\dfrac{1}{3}}^{n-1}\\a_n = (27)\times ({\dfrac{1}{3}})^{n-1}[/tex]
Therefore, the correct option is B.
Learn more about Substituting Geometric Progression:
https://brainly.com/question/14320920
What is 8+0.0+0.05+0.009+0.0006 in standard form
Without using a calculator, determine between which two consecutive integers the square root lies _/29
5 and 6
√25 = 5 and √36 = 6
5 < √29 < 6
A car can travel 105 miles on 7 gallons of gas. How far can it travel on 9 gallons
Find how far the car can travel on one gallon of gas, by dividing total miles by number of gallons:
105 miles / 7 gallons = 15 miles per gallon.
Now multiply that by the number of gallons to find total miles:
15 miles per gallon x 9 gallons = 135 total miles.
RS=6y+5,ST=2y-3, and RT=12y-14
Find Y.
._______.___.
R S T
Note that RT is the whole line segment, and RS and ST are parts of it
RS = 6y + 5
ST = 2y - 3
RT = 12y - 14
Set the equation
RS + ST = RT
(6y + 5) + (2y - 3) = 12y - 14
Simplify. Combine like terms
6y + 2y + 5 - 3 = 12y - 14
(6y + 2y) + (5 - 3) = 12y - 14
8y + 2 = 12y - 14
Note the equal sign. What you do to one side, you do to the other. Isolate the variable (y). Subtract 12y from both sides, and 2 from both sides.
8y (-12y) + 2 (-2) = 12y (-12y) - 14 (-2)
8y - 12y = -14 - 2
Simplify. Combine like terms
(8y - 12y) = (-14 - 2)
-4y = -16
Isolate the y. Divide -4 from both sides
-4y/-4 = -16/-4
y = (-16)/-4
y = 4
--------------------------------------------------------------------------------------------------------------------------
4 is your answer for y.
--------------------------------------------------------------------------------------------------------------------------
hope this helps
What is 6x+2=9x-1 ahngfhwejgfjhygfweugfuweg
By simplifying both sides of the equation, then isolating the variable.
x = 1
Answer:
x=1
Step-by-step explanation:
1. Move the terms: move the variable to the left hand side and change it sign
2. Move the constant to the right hand side and change its sign
3. Collect like terms
4. Calculate the difference
5. Divide both sides of the equation by -3, therefore x = 1
please mark brainliest! :)
A hayride costs $8 per person, and there is a 25% discount for children, students, and senior citizens. If there are (p) people who do not qualify for the discount and (s) people who do qualify, which equation can be used to calculate the revenue (R)?
A R = 8p - 6s
B R = 8p + (0.75)(8)(s)
C R = 8p + 0.75s
D R = 8p + (0.25)(8)(s)
the answer for this question is D
Write three numbers that are greater than 12,000 but less than 13,000
The answers to your question are,
12,001, 12,562, 12,999
-Mabel <3
12,001, 12,562, 12,999 .
Is your answers, hope this helps.
~hEcKiNsHoBe
Find the mean of the data set.
–17 32 –9 0 52 12 –14
a.8
b.9.3
c.0
d.–6.8
A. 8 would be your answer. add all the numbers up, and divide by how many numbers there are.
Rosa's test scores are 78, 92, 88, and 89. What must she score on her next test to have an average of 90? A) 95 B) 97 C) 99 D) 103
Answer: D
Step-by-step explanation:
Let x represent the score on her next test
[tex]\frac{78 + 92 + 88 + 89 + x}{5} = 90[/tex]
[tex](5)\frac{78 + 92 + 88 + 89 + x}{5} = (5)90[/tex]
78 + 92 + 88 + 89 + x = 5(90)
347 + x = 450
-347 -347
x = 103
CAN SOMEONE JUST PLEASE ANSWER THIS ASAP FOR BRAINLIEST!!’
The volume (in cubic meters), v, of a rectangular room is given by the expression:
v = 162 - 2b^6
Where b is a positive integer and each dimension is an integer greater than 1 meter. What are three unique expressions that could represent the dimensions of the room in terms of b?
Write these three expressions as a product that equals the volume (e.g. "(expression 1)(expression 2)(expression 3)").
An expression involves subtracting two numbers from a given first number under what circumstance will the value of the expression be negative
Final answer:
The value of an expression will be negative when the sum of the two numbers subtracted from a given first number is greater than the initial number itself, resulting in a negative outcome after applying the appropriate rules for addition and subtraction.
Explanation:
The value of an expression involving the subtraction of two numbers from a given first number will be negative under specific conditions. When the combination of the two numbers to be subtracted is larger than the first number, the result will be negative. To understand this, let's consider the basic rules of addition and subtraction with positive and negative numbers:
When two positive numbers add, the result has a positive (+ve) sign. For example, 3+2 = 5.When two negative numbers add, the result has a negative (−ve) sign. For example, -4 + (-2) = -6.When two numbers having opposite signs add, subtract the smaller number from the larger number, and the result has the sign of the larger number. For example, -5 + 3 = -2.In subtraction, we change the sign of the number being subtracted and then apply the rules of addition:
5 - (+3) = 5 - 3 = 2, where the sign of 3 is changed from positive to negative before adding.2 - (-6) = 2 + 6 = 8, where the sign of -6 is changed to positive before adding.Therefore, to have a negative result, the magnitude of the sum of the two numbers being subtracted should exceed the first number and, reflecting the sign rules, should result in a negative value. For instance, if the first number is 1 and the two numbers to subtract are 3 and 5, the expression would be 1 - (3 + 5) = 1 - 8 = -7, resulting in a negative value.
Kaori is taking a free-throw. H(d) models the basketball's height (in meters) at a horizontal distance of d meters from Kaori. What does the statement H(R)=4H mean?
Answer: The statement H(R)=4H means the height of ball is 4H meter at a horizontal distance of R meters from Kaori.
Explanation:
It is given that Kaori is taking a free-throw. H(d) models the basketball's height (in meters) at a horizontal distance of d meters from Kaori.
The given statement is H(R) = 4H.
Here we have H(R) instead of H(d) and it shows the height of basketball. So it clear that the height of basketball's is 4H because H(R)=4H at d = R
Since d represents the horizontal distance from Kaori, therefore the horizontal distance from Kaori is R.
Thus, Answer: The statement H(R)=4H means the height of ball is 4H meter at a horizontal distance of R meters from Kaori.
Answer:
At a horizontal distance of RRR meters from Kaori, the ball's height was equal to 444 meters.
Step-by-step explanation:
What is 0.79 x 3.7 with an explanation?
My answer for 0.79 x 3.7 is 2.923. It is 2.923 because when you do the problem on paper that is what you get. Also not to be rude or nothing im good at math.
[tex]Solution, 0.79\cdot \:3.7=2.923[/tex]
[tex]Steps:[/tex]
[tex]\mathrm{Multiply\:without\:the\:decimal\:points,\:then\:put\:the\:decimal\:point\:in\:the\:answer}, 79\cdot \:37=2923[/tex]
[tex]79\cdot \:37, \mathrm{Line\:up\:the\:numbers}, \begin{matrix}\space\space&7&9\\ \mathrm{x}&3&7\end{matrix}[/tex]
[tex]\mathrm{Multiply\:the\:top\:number\:by\:the\:bolded\:digit\:of\:the\:bottom\:number}, \begin{matrix}\space\space&\textbf{7}&\textbf{9}\\ \mathrm{x}&3&\textbf{7}\end{matrix}[/tex]
[tex]\mathrm{Mutliply\:the\:bold\:numbers}:\quad \:9\cdot \:7=63[/tex][tex]\mathrm{Carry\:}6\mathrm{\:to\:the\:column\:on\:the\:left\:and\:write\:}3\mathrm{\:in\:the\:result\:line}[/tex][tex]\frac{\begin{matrix}\space\space&6&\space\space\\ \space\space&7&\textbf{9}\\ \mathrm{x}&3&\textbf{7}\end{matrix}}{\begin{matrix}\space\space&\space\space&3\end{matrix}}[/tex]
[tex]\mathrm{Add\:the\:carried\:number\:to\:the\:multiplication}:\quad \:6+7\cdot \:7=55[/tex], [tex]\mathrm{Carry\:}5\mathrm{\:to\:the\:column\:on\:the\:left\:and\:write\:}5\mathrm{\:in\:the\:result\:line}, \frac{\begin{matrix}\space\space&5&\textbf{6}&\space\space\\ \space\space&\space\space&\textbf{7}&9\\ \mathrm{x}&\space\space&3&\textbf{7}\end{matrix}}{\begin{matrix}\space\space&\space\space&5&3\end{matrix}}[/tex]
[tex]\mathrm{Add\:the\:carried\:digit,\:}5\mathrm{,\:to\:the\:result}, \frac{\begin{matrix}\space\space&5&6&\space\space\\ \space\space&\space\space&7&9\\ \mathrm{x}&\space\space&3&7\end{matrix}}{\begin{matrix}\space\space&5&5&3\end{matrix}}[/tex]
[tex]\frac{\begin{matrix}\space\space&\space\space&\textbf{7}&\textbf{9}\\ \space\space&\mathrm{x}&\textbf{3}&7\end{matrix}}{\begin{matrix}\space\space&5&5&3\end{matrix}}[/tex]
[tex]\frac{\begin{matrix}\space\space&\space\space&2&\space\space\\ \space\space&\space\space&7&\textbf{9}\\ \space\space&\mathrm{x}&\textbf{3}&7\end{matrix}}{\begin{matrix}\space\space&5&5&3\\ \space\space&\space\space&7&\space\space\end{matrix}}[/tex]
[tex]\frac{\begin{matrix}\space\space&2&\textbf{2}&\space\space\\ \space\space&\space\space&\textbf{7}&9\\ \mathrm{x}&\space\space&\textbf{3}&7\end{matrix}}{\begin{matrix}\space\space&5&5&3\\ \space\space&3&7&\space\space\end{matrix}}[/tex]
[tex]\frac{\begin{matrix}\space\space&2&2&\space\space\\ \space\space&\space\space&7&9\\ \mathrm{x}&\space\space&3&7\end{matrix}}{\begin{matrix}\space\space&5&5&3\\ 2&3&7&\space\space\end{matrix}}[/tex]
[tex]\frac{\begin{matrix}\space\space&\space\space&7&9\\ \space\space&\mathrm{x}&3&7\end{matrix}}{\begin{matrix}0&5&5&3\\ 2&3&7&0\end{matrix}}[/tex]
553+2370=2923, =2.923
What is 2+2.
15 points
Get it right
ITS 4!! THE ANSWE IS 4!!! BRAINLIEST?!?!
5ac+10ab-2c^2-4bc
Factor.
Final answer:
The expression 5ac+10ab-2c²-4bc is factored by first taking out the common factor of 2, and then grouping terms to extract 'a' from the first two and 'c' from the last two terms to get 2(a(5c + 5b) - c(c + 2b)).
Explanation:
To factor the expression 5ac+10ab-2c²-4bc, we look for common factors in each term. Observing the coefficients, we see that each term is divisible by 2. Also, we can factor out variable 'a' from the first two terms and variable 'c' from the last two terms. The factored expression is:
2a(5c + 5b) - 2c(c + 2b).
We can then extract the common factor 2 from both parts to get:
2(a(5c + 5b) - c(c + 2b)).
This is the fully factored form of the given expression.
A local club team is holding tryouts for six spots on the soccer team. Since there is not much time before a very important tournament they need to select the best players. Which method would be the best to ensure they select the "most talented" soccer players?
The method would be the best to ensure they select the "most talented" soccer players is They watch the players during tryouts and then put them on a list in order from the most skilled to the least skilled and then select the top six from the list.
The correct option is (A).
A. This method involves observing the players during tryouts and then ranking them from the most skilled to the least skilled. By selecting the top six players from this ranked list, the team is more likely to pick the most talented individuals based on their performance and skills demonstrated during the tryouts.
Option B (selecting the first six that show up) may not necessarily guarantee selecting the most talented players as eagerness to show up early does not always correlate with soccer skills.
Option C (selecting randomly from a hat) is not ideal because it does not take into account the players' actual skills and performance during tryouts. It relies solely on chance.
Option D (selecting the top three and bottom three) may overlook potentially talented players who fall in the middle range. Additionally, selecting the bottom three solely based on being the least skilled may not be fair or accurate.
Therefore, option A is the most suitable method for ensuring the selection of the "most talented" soccer players.
complete question given below:
A local club team is holding tryouts for six spots on the soccer team. Since there is not much time before a very important tournament they need to select the best players. Which method would be the best to ensure they select the "most talented" soccer players?
A. They watch the players during tryouts and then put them on a list in order from the most skilled to the least skilled and then select the top six from the list.
B. The first day of tryouts they select the first six that show up as they figure those are the most eager for a spot.
C. They place all of the names of the people trying out in a hat and theselect six out of the hat. Those are the ones that are chosen.
D. They watch the players during tryouts and then put them on a list in order from the most skilled to the least skilled and then select the top three and the bottom three from the list.
Utilize open tryouts, structured evaluations, scouting, fitness assessments, game simulations, background checks, objective evaluation, expert consultation, feedback, and review.
To ensure the selection of the most talented soccer players for the local club team, the following method can be adopted:
1. **Open Tryouts**: Organize open tryouts where any interested player can participate. This allows for a wide pool of talent to be assessed.
2. **Structured Evaluation**: Develop a structured evaluation system that includes various aspects of soccer skills such as dribbling, passing, shooting, defending, and game intelligence. Each player should be assessed on these criteria.
3. **Scouting**: Utilize scouts who have a keen eye for talent to observe players in local leagues, school teams, or other relevant competitions. They can provide insights into players who may not have attended the tryouts.
4. **Physical Fitness Assessment**: Soccer requires a good level of physical fitness. Conduct physical fitness assessments to gauge players' endurance, speed, agility, and strength.
5. **Game Simulations**: Organize scrimmages or small-sided games during tryouts to see how players perform in real-game situations. This can reveal their decision-making abilities, teamwork skills, and adaptability.
6. **Background Checks**: Consider players' past performances, achievements, and behavioral aspects. Look for players who demonstrate dedication, discipline, and a positive attitude.
7. **Objective Evaluation**: Ensure that the selection process is fair and transparent, with scores and assessments being recorded objectively. Avoid biases based on personal preferences or relationships.
8. **Consult Coaches and Experts**: Involve experienced coaches or soccer experts in the selection process. They can provide valuable insights and perspectives on players' potential and suitability for the team.
9. **Feedback and Review**: Provide feedback to players after the tryouts, highlighting areas of improvement and offering guidance for future development. Additionally, periodically review the selected players' performance to ensure they continue to meet the team's standards.
By combining these methods, the local club team can maximize the chances of selecting the most talented soccer players for their upcoming tournament.
Can someone Please help with this Geometry question, thanks!
The length of CD is -9 to 7 = 16 units long
CE is 1/4 of that length, so 16 x 1/4 = 4 units long.
Add 4 to C: -9 + 4 = -5
Point E would be located at -5.
The line for which equation has a negative slope?
A. y = 6
B. y = -5x
C. y = 2x + 5
What is the slope of the line represented by -14y = 7x ?
A. −2
B. 1/2 negative
C. 2
Question 3
What is the approximate solution of the following system of equations?
graph of lines y equals negative x minus 5 and y equals x plus 9
(2, -7)
(-7, 2)
(7, 2)
(-7, -2)
answer is (-7,2)
y = -x -5
y= x+9
Both equations have y on the left hand side
So we equate both equations
We replace -x-5 for y in the second equation
-x -5 = x+9
Subtract x on both sides
-2x -5 = 9
Now add 5 on both sides
-2x = 14
Divide by -2 from both sides
x = -7
Now plug in -7 for x in the first equation
y = -x -5
y = -(-7) -5= 7-5 = 2
So answer is (-7,2)
1. You have the following system of equations:
[tex]\left \{ {{y=-x-5} \atop {y=x+9}} \right.[/tex]
2. Therefore, you have that [tex]y=y[/tex], then:
[tex]-x-5=x+9[/tex]
3. Solve for [tex]x[/tex]:
[tex]-5-9=x+x\\2x=-14\\x=-7[/tex]
3. Now, substitute this value into one the original equations:
[tex]y=x+9\\y=-7+9\\y=2[/tex]
The answer is: (-7,2)
Which equations are correct? Select each correct answer. −5a4(2a2+4)=−10a6−20a4 −4x2(2x2+5)=−8x4−20x2 −6y4(4y2+2)=−24y8−12y4 −4b3(5b2+3)=−20b6−12b3
1. Consider the expression [tex]-5a^4(2a^2+4)=-10a^6-20a^4.[/tex]
Start with left side and use dustributive property :
[tex]-5a^4(2a^2+4)=-5a^4\cdot 2a^2-5a^4\cdot 4=-10a^6-20a^4.[/tex]
This option is true.
2. Consider the expression [tex]-4x^2(2x^2+5)=-8x^4-20x^2.[/tex]
Start with left side and use dustributive property :
[tex]-4x^2(2x^2+5)=-4x^2\cdot 2x^2-4x^2\cdot 5=-8x^4-20x^2.[/tex]
This option is true.
3. Consider the expression [tex]-6y^4(4y^2+2)=-24y^8-12y^4.[/tex]
Start with left side and use dustributive property :
[tex]-6y^4(4y^2+2)=-6y^4\cdot 4y^2-6y^4\cdot 2=-24y^6-12y^4\neq -24y^8-12y^4.[/tex]
This option is false.
4. Consider the expression [tex]-4b^3(5b^2+3)=-20b^6-12b^3.[/tex]
Start with left side and use dustributive property :
[tex]-4b^3(5b^2+3)=-4b^3\cdot 5b^2-4b^3\cdot 3=-20b^5-12b^3\neq -20b^6-12b^3.[/tex]
This option is false.
Answer: A, B - true, C, D - false.
Answer
−5a⁴(2a²+4)=−10a⁶−20a⁴ is correct.
−4x²(2x²+5)=−8x⁴−20x² is correct.
−6y⁴(4y²+2)=−24y⁸−12y⁴ is NOT correct.
−4b³(5b²+3)=−20b⁶−12b³ is NOT correct.
Explanation
Equation 1
−5a⁴(2a²+4)=−10a⁶−20a² ⇒ −5a⁴(2a²+4) = ( −5a⁴×2a²)+ ( −5a⁴×4)
= -10a⁶ - 20a⁴
−5a⁴(2a²+4)=−10a⁶−20a² is correct
Equation 2
−4x²(2x²+5)=−8x⁴−20x² ⇒ −4x²(2x²+5) = (-4x²×2x²) + (-4x²×5)
= -8x⁴ - 20x²
−4x²(2x²+5)=−8x⁴−20x² is correct.
Equation 3
−6y⁴(4y²+2)=−24y⁸−12y⁴ ⇒ −6y⁴(4y²+2) = (−6y⁴×4y²) + (-6y⁴×2)
= -24y⁶ - 12y⁴
−6y⁴(4y²+2)=−24y⁸−12y⁴ is NOT correct.
Equation 4
−4b³(5b²+3)=−20b⁶−12b³ ⇒ −4b³(5b²+3) = (−4b³×5b²) + (-4b³×3)
= -20b⁵ - 12b³
−4b³(5b²+3)=−20b⁶−12b³ is NOT correct.